Pengaruh Media Sosial Terhadap Hasil Belajar Mahasiswa Program Studi Teknologi Informasi Semester 1 - Telaumbanua, Elvi Ningsih; Zai, Enitia (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Social media has become important in daily life, especially to help students learn, thanks to the advancement of information and communication technology in the digital era. The purpose of this study is to analyze the influence of social media use on the learning outcomes of 1st semester students of the Information Technology Study Program at the University of Nias. With a quantitative approach and survey method, this study collected data from 47 respondents through a questionnaire to measure the duration of social media use and its impact on students' learning focus. Data analysis was carried out using a correlation test to determine the relationship between variables of social media use and learning concentration. The results showed that although the majority of students used social media for only 1-2 hours per day, there was little significant disruption, with a correlation value of 0.221. Based on these findings, it is recommended that students manage the time they use social media wisely to optimize the quality of learning. This research also emphasizes the importance of digital literacy so that social media can be used as a tool that supports education, not an obstacle.